Charged polystyrene microplastics inhibit uptake and transformation of 14C-triclosan in hydroponics-cabbage system - Enguang Nie; Yandao Chen; Shengwei Xu; Zhiyang Yu; Qingfu Ye; Qing X. Li; Zhen Yang; Haiyan Wang (Journal of Advanced Research)
Introduction: Since the outbreak of COVID-19, microplastics (MPs) and triclosan in pharmaceuticals and personal care products (PPCPs) are markedly rising. MPs and triclosan are co-present in the environment, but their interactions and subsequent implications on the fate of triclosan in plants are not well understood. Objective: This study aimed to investigate effects of charged polystyrene microplastics (PS-MPs) on the fate of triclosan in cabbage plants under a hydroponic system. Methods: 14C-labeling method and liquid chromatography coupled with quadrupole/time-of-flight mass spectrometry (LC-QTOF-MS) analysis were applied to clarify the bioaccumulation, distribution, and metabolism of triclosan in hydroponics-cabbage system. The distribution of differentially charged PS-MPs in cabbage was investigated by confocal laser scanning microscopy and scanning electron microscopy. Results: The results showed that MPs had a significant impact on bioaccumulation and metabolism of triclosan in hydroponics-cabbage system. PS-COO-, PS, and PS-NH3+ MPs decreased the bioaccumulation of triclosan in cabbage by 69.1 %, 81.5 %, and 87.7 %, respectively, in comparison with the non-MP treatment (control). PS-MPs also reduced the translocation of triclosan from the roots to the shoots in cabbage, with a reduction rate of 15.6 %, 28.3 %, and 65.8 % for PS-COO-, PS, and PS-NH3+, respectively. In addition, PS-NH3+ profoundly inhibited the triclosan metabolism pathways such as sulfonation, nitration, and nitrosation in the hydroponics-cabbage system. The above findings might be linked to strong adsorption between PS-NH3+ and triclosan, and PS-NH3+ may also potentially inhibit the growth of cabbage. Specially, the amount of triclosan adsorbed on PS-NH3+ was significantly greater than that on PS and PS-COO-. The cabbage biomass was reduced by 76.9 % in PS-NH3+ groups, in comparison with the control. Conclusion: The uptake and transformation of triclosan in hydroponics-cabbage system were significantly inhibited by charged PS-MPs, especially PS-NH3+. This provides new insights into the fate of triclosan and other PPCPs coexisted with microplastics for potential risk assessments.